Permanences bilatérales dans l’aide au développement en Afrique subsaharienne - Thierry Simon (EchoGéo)
The African continent has just experienced fifty years of aid for development that began shortly after its different countries had obtained their own independence. This period witnessed the piling up of a formidable amount of budgetary help and various sectorial programmes, with a wealth of projects and micro-projects. Drawing on the hindsight of this last half-century, this paper attempts to focus on the process of French and British bilateral aid within the nebula of this expansion. Particular attention will be paid to the development of the territorial zones, where this financial assistance was granted and the projects that benefited from a large part of it in the context of nationwide frameworks. Bilateral aid is always vulnerable and the source of much controversy and debate. It continues to endure by adjusting to meet changing circumstances and may well find renewed vigour in the context of a background coloured by the rising of new bilateral players.